REACTIVE IRON(III) IN SEDIMENTS: CHEMICAL VERSUS MICROBIAL EXTRACTIONS - Hyacinthe C.; Bonneville S.; Van Cappellen P. (My University, 2006)
The availability of particulate Fe(III) to iron reducing microbial communities in sediments and soils is generally inferred indirectly by performing chemical extractions. In this study, the bioavailability of mineral-bound Fe(III) in intertidal sediments of a eutrophic estuary is assessed directly by measuring the kinetics and extent of Fe(III) utilization by the iron reducing microorganism Shewanella putrefaciens, in the presence of excess electron donor. Microbial Fe(III) reduction is compared to chemical dissolution of iron from the same sediments in buffered ascorbate-citrate solution (pH 7.5), ascorbic acid (pH 2), and 1 M HCl. The results confirm that ascorbate at near-neutral pH selectively reduces the reactive Fe(III) pool, while the acid extractants mobilize additional Fe(II) and less reactive Fe(III) mineral phases. Furthermore, the maximum concentrations of Fe(III) reducible by S. putrefaciens correlate linearly with the iron concentrations extracted by buffered ascorbate-citrate solution, but not with those of the acid extractions. However, on average, only 65% of the Fe(III) reduced in buffered ascorbate-citrate solution can be utilized by S. putrefaciens, probably due to physical inaccessibility of the remaining fraction of reactive Fe(III) to the cells. While the microbial and abiotic reaction kinetics further indicate that reduction by ascorbate at near-neutral pH most closely resembles microbial reduction of the sediment Fe(III) pool by S. putrefaciens, the results also highlight fundamental differences between chemical reductive dissolution and microbial utilization of mineral-bound ferric iron.
Keywords: BIOAVAILABILITY; ESTUARINE SEDIMENT; IRON-REDUCING BACTERIUM; MICROBIAL ACTIVITY; MICROBIAL COMMUNITY; REACTION KINETICS; SHEWANELLA PUTREFACIENS